uji aktivitas antijamur ekstrak etanol daun sirsak terhadap jamur penyebab penyakit kulit - masayu ayu azizah (Jurnal Penelitian Farmasi Indonesia)
Abstract - The test of antifungal actifity of ethanol extract of soursop leaf (Annona muricata L.) to Triciohyton rubrum, Tricophyton mentagrophytes, Epidermophyton floccosum, Microsporum canis and Malassezia furfur. This study aims to prove the inhibition from ethanol extract of soursoup leaf (Annona muricata L.) to the growth of fungi causing skin diseases. The antifungal activity test of soursop leaf extract using diffusion method, with concentration of 40%, 50%, 60%, positive control of ketoconazole and negatif control of ethanol distillate. The result showed the average inhibitory zone diameter of Tricophyton rubrum(7,06 mm, 8,56 mm, and 11,13 mm), Tricophyton mentagrophytes (7,26 mm, 8,76 mm and 11 mm), Epidermophyton floccosum (16 mm, 8,6 mm and 11,33 mm), Microsporum canis (7,56 mm, 8,63 mm, and 12,16 mm) and Malassezia furfur(8,36 mm, 9,2 mm and 12,33 mm). It can be concluded that soursop leaf extract (Annona muricata L.) has antifungal activity against Triciohyton rubrum, Tricophyton mentagrophytes, Epidermophyton floccosum, Microsporum canis and Malassezia furfur. The largest antifungal activity is Malassezia furfur at a concentration of 60% with a diameter of 12,33 mm inhibition. Keywords : Soursop Leaf Extracts Ethanol, Anti-fungal, Skin Diseases.